The Role of Communication Interaction Within the Regional Organization of the North Sumatra Student Association in Alleviating Homesickness Experiences Among New Migrant Students (Literasi Nusantara, 2025)
This study explores the role of communication interactions within the Ikatan Mahasiswa Sumatera Utara (IKAMASU) regional student organization in alleviating homesickness among first-year migrant students at Universitas Trunojoyo Madura. Using a qualitative phenomenological approach, data were collected from purposively selected first-year North Sumatran students and organizational administrators through semi-structured interviews, participant observation, and documentation; data were analyzed following a Moustakas-inspired phenomenological procedure with method triangulation to ensure credibility. Findings show that IKAMASU functions as a family-like social space where intensive verbal exchanges (often in regional language), supportive nonverbal behaviors (open posture, empathic gestures), senior-member mentoring, and continuous digital communication together create emotional security and a sense of belonging. These communication processes reduce loneliness, normalize homesickness as a shared experience, and facilitate students’ psychological and social adaptation to campus life. The study concludes that structured, identity-based peer interaction within regional student organizations constitutes an effective social-support mechanism for mitigating homesickness and improving early university adjustment; universities should recognize and strengthen such community networks as part of student well-being initiatives.